2014
DOI: 10.1007/978-3-319-06995-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Thermo-Mechanical Behavior of Ti2AlC MAX Phase and Fiber Reinforced Ti2AlC Composites

Abstract: Ti 2 AlC MAX phase samples were processed by using Spark Plasma Sintering from commercially available Ti 2 AlC powder. Static and dynamic loading was performed by Universal Testing Machine and Split Hopkinson Pressure Bar (SHPB) respectively. The SHPB apparatus was modified to investigate the dynamic fracture initiation toughness. High speed photography was used to determine the fracture initiation time and the associated failure load. To widen applications, 20 vol % fiber of NextelTM-610 and NextelTM-720 have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…However, limited work has been performed to investigate the toughening behaviors of fiber- or whisker-reinforced MAX phases due to the high reactivity between the fibers and MAX phase matrix. Most of the work focused on the fabrication of the whisker or fiber/MAX phase composites and the main fibers include SiC fiber [31,32,33], carbon fiber [34] and Al 2 O 3 fiber [35,36]. …”
Section: Toughening In Nanolayered Max Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, limited work has been performed to investigate the toughening behaviors of fiber- or whisker-reinforced MAX phases due to the high reactivity between the fibers and MAX phase matrix. Most of the work focused on the fabrication of the whisker or fiber/MAX phase composites and the main fibers include SiC fiber [31,32,33], carbon fiber [34] and Al 2 O 3 fiber [35,36]. …”
Section: Toughening In Nanolayered Max Phasesmentioning
confidence: 99%
“…Furthermore, Ti 2 AlC matrix loaded with two type of Al 2 O 3 fibers (20 vol %) was obtained by spark plasma sintering (named as Ti 2 AlC/720f and Ti 2 AlC/610f) [ 36 ]. The fracture experiments and the post-mortem analysis of the fracture surface by SEM revealed that kinking along with intergranular cracking and delamination played an important role in deformation of Ti 2 AlC.…”
Section: Toughening In Nanolayered Max Phasesmentioning
confidence: 99%
“…Dash et al reported an increase in the high-temperature creep resistance of Ti 3 SiC 2 when reinforced with SiC (w) [15] and short SiC (f) [16], the former presumably being due to hindered grain boundary sliding. The reinforcement of Ti 2 AlC with Al 2 O 3(f) also resulted in improved thermomechanical properties, with an increase in the compressive fracture strength of up to 39.7% as compared to monolithic Ti 2 AlC [17]. Furthermore, the addition of SiC (f) to Cr 2 AlC led to a 70-80% increase in its wear resistance and a reduction in the friction coefficient up to 20% [18].…”
Section: Introductionmentioning
confidence: 97%
“…In fact, several studies [15][16][17][18] into fiber and whisker-reinforced MAX phases demonstrated their superior thermomechanical response. Most often, the use of silicon carbide fibers (SiC (f) ), as well as whiskers (SiC (w) ), and alumina fibers (Al 2 O 3(f) ), have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, Ti 2 AlC has been reinforced with 20 vol.% of NextelTM-610 and NextelTM-720 alumina fibers. 16 The compressive failure stress in dynamic conditions decreases with increasing temperature, from 1645 MPa at 25℃ to 1210 MPa at 1200℃. In addition, compressive fracture strength of Ti 2 AlC/720 and Ti 2 AlC/610 composites was enhanced by 39.7% and 32.6% under static loading in comparison with the monolithic Ti 2 AlC.…”
Section: Introductionmentioning
confidence: 98%